Evaluation method for building performance in Light Wood Frame in Brazil - Sotsek, Nicolle Christine (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2020)
Light wood frame (LWF) is a construction system considered innovative in Latin American countries, which has been used as a strategy to mitigate housing deficits. Since this construction system is new in these countries, a rigorous assessment of their manufacturing, construction and use is essential. Thus, this research aims to develop a method to evaluate the performance of LWF buildings in Brazil to help builders optimise the construction system in the country. The study made use of the literature to identify valuable criteria for a building performance evaluation using qualitative tools, such as questionnaires and the Delphi technique, to select specific criteria for the LWF system. Finally, statistic tools, criteria groups and weights were generated. As a result, the study established a framework with 5 dimensions, 19 criteria and 41 sub-criteria, thus understanding which the most important criteria are to be evaluated during the LWF building performance evaluation. Finally, the criteria with the highest scores refer to structural durability, maintenance, sealing and control of thermal, acoustic, visual and air quality comfort.